A Competitive Objective Structured Clinical Examination Event to Generate an Objective Assessment of Anesthesiology Resident Skills Development. Issue 10 (15th May 2016) - Rebel, Annette; DiLorenzo, Amy N.; Fragneto, Regina Y.; Dority, Jeremy S.; Rose, Greg; Nguyen, Dung; Hassan, Zaki-Udin; Schell, Randall M.
Abstract : Residency programs are charged with teaching, assessing, and documenting resident competency for a multitude of skills throughout the course of residency training. An innovative, competition-based objective structured clinical examination event was designed in our department to objectively assess the skill level of anesthesiology residents. After conducting the identical event for 2 years in postgraduate year 1 (PGY1) and postgraduate year 2 (PGY2) residents, we tested the hypothesis that the event can provide adequate standardization to appropriately document progression in technical and nontechnical skills. Twenty-one residents participated in both events during their PGY1 and PGY2 years: n = 10, 2012/2013, n = 11, 2013/2014. The PGY1 participants in 2012 were retested in 2013 (as PGY2 residents) during an identical event, and their performance was compared as a group and on an individual level. The PGY1 residents in 2013 did the same in 2014. Four workstations were analyzed to determine whether improvement in performance occurred between the PGY1 and the PGY2 years: (1) preoperative assessment, (2) operating room anesthesia station checkout, (3) peripheral IV and endotracheal tube placement, and (4) transfer of care in the postanesthesia care unit. The performances of PGY1 and PGY2 residents were compared. The assessments were performed by anesthesiology faculty using checklists, time to complete task, and Likert scale ratings. Data analysis showed improved technical anesthesia skills (operating room setup, peripheral IV, and endotracheal tube placement) and more complete anesthesia-related information management in the preoperative assessment and postoperative transition of care in the postanesthesia care unit in PGY2 residents compared with the PGY1 performance of the same residents. The described event is a valuable tool for objective assessment of multiple anesthesia skills and possible milestones during residency.